Pengaruh Penambahan Serbuk Gergaji Kayu Jati (Tectona Grandis L.F.) pada Mortar Semen Ditinjau Dari Kuat Tekan dan Daya Serap Air - Suroso, Hery (Semarang State University, 2006)
Abstract: Due to the fact that the price of materials of building becomes more expensive, while the larger waste of industrial foresty can not be used optimally yet, thus it is necessary to make a research in terms the use of waste process of forestry industries, especially waste of saw dust as content material in cement mortar. It is expected to obtion benefits such as increasing additional and useful values of material, diversity of constructional material types, promoting material existence and much less overcoming negative effect wood industrial waste. Cement mortar with mixture of saw dust relatively has low heat and electrical conductivity, has isolator characteristic and good acoustic, so this material is compatible for soundproof room. In this research, morlar was made from Muntilan sand, Nusantara Cement type I and Teak wood dust (Tectona Grandis L.F.) which comes from saw wood industries in Sarip village's, subdistrict in Wirosari, Grobogan Regency, Purwodadi. Object experiment that already has made from this research shape is cube, size of 50X50X50 mm3. The result shows that spread values in the field was 95% - 103.5% with w/c value which resulted (from 0%-20% saw dust to the weight of sand and weight of cement) continued between 1.05- 1.10. The decreasing of stress mortar cement is subtitute weight of sand from 0% up to 20% saw dust, from 128. 740 kg/cm2 becomes 15. 279 kg/cm2, while the stress mortar cement is substitute with weight of cement from 0% up to 20% saw dust from 113.84 kg/cm2 becomes 45. 070kglcm2. The increasing water absorption mortar cement is substitute weight of sand from 0% up to 20% saw dust from 9.569% becomes 46.481% while water absorption mortar cement is substitute weight of cement from 0% up to 20% saw dust from 11.013% becomes 16.015%.Abstrak: Melihat kenyataan bahwa semakin mahalnya harga bangunan, sementara limbah industri kehutanan yang begitu besar belum sepenuhnya dapat dimanfaatkan, maka perlu dilakukan penelitian yang berkaitan dengan masalah pemanfaatan limbah industri kehutanan, khususnya limbah serbuk gergaji sebagai isian pada mortarv semen. Dengan pemanfaatan tersebut diharapkan diperoleh keuntungan antara lain meningkatkan nilai tambah dan nilai guna bahan, diversifikasi jenis bahan konstruksi, menunjang pengadaan bahan dan sedikit banyak dapat mengatasi dampak negatif limbah industri kayu. Mortar semen dengan bahan campuran serbuk gergaji memiliki daya hantar panas dan listrik yang relatif rendah, mempunyai sifat isolasi dan akustik yang baik sehingga bahan ini cocok untuk ruang kedap suara. Pada penelitian ini mortar dibuat dari pasir Mutilan, Semen Nusantara type 1 dan serbuk gergaji kayu jati (Tectona grandis L.F.) yang didatangkan dari pabrik penggergajian kayu di Desa Sarip Kecamatan Wirosari Kabupaten Grobogan, Purwodadi. Benda uji yang dibuat dalam penelitian ini berbentuk kubus dengan ukuran 50X50X50 mm3. Hasil penelitian menunjukkan bahwa nilai sebar dilapangan sebesar 95% - 103% dengan nilai fas yang dihasilkan (dari 0% hingga 20% serbuk gergaji terhadap berat pasir dan berat semen) berturut-turut bernilai antara 1,05 - 1,10. Penurunan nilai kuat tekan mortar semen substitusi berat pasir dari 0% hingga 20% serbuk gergaji dari 128,740 kg/cm2 menjadi 15,279 kg/cm2 sedangkan nilai kuat tekan mortar semen substitusi berat semen dari 0% hingga 20% serbuk gergaji dari 113,84 kg/cm2 menjadi 455,070 kg/cm2. Peningkatan daya serap air mortar semen substitusi berat pasir dari 0% hingga 20% serbuk gergaji dari 9,569% menjadi 46,481 % sedangkan nilai daya serap air mortar semen substitusi berat semen dari 0% hingga 20 % serbuk gergaji dari 11,013 % menjadi 16,015 %